Study of Single-dose Toxicity of Guseonwangdo-go Glucose Intramuscular Injection in Sprague-Dawley Rats - Jo, Su-jeong; Kim, Sung-chul; Kim, Yu-jong; Kim, Eun-jung; Kim, Kap-sung; Lee, Seung-deok (Journal of pharmacopuncture, 2014)
This study was performed to analyze single-dose intramuscular toxicity of Guseonwangdo-go glucose pharmacopuncture. Eighty six-week-old Sprague-Dawley rats were divided into two large groups of forty rats; Guseonwangdo-go glucose 5% and Guseonwangdo-go glucose 20% groups. Each group was sub-divided into four smaller groups of five males and five females, with the following dosages of pharmacopuncture being administered by intramuscular (IM) injection in each group: group 1 (G1, control group): 1.0 mL of normal saline solution, group 2 (G2, low-dose group): 0.1 mL, group 3 (G3, mid-dose group): 0.5 mL, and group 4 (G4, high-dose group): 1.0 mL. No mortalities or clinical signs were observed in any group. Also, no significant changes in body weights or in hematological/biochemical analyses were observed between the control and the experimental groups during necropsy or histopathology. The above findings suggest that the lethal dose of Guseonwangdo-go glucose 5% and 20% pharmacopuncture administered via IM injection is more than 1.0 mL per animal in both male and female rats. Further studies on the repeated-dose toxicity of Guseonwangdo-go glucose should be conducted to yield more concrete data.